A voz narrativa em O fim de Eddy (2018) e Quem matou meu pai (2023), de Édouard Louis - Gonçalves, Rodrigo Matos da Silva (2025)
In this research, we aimed to investigate the characteristics of the narrative voice of the Édouard Louis’ literary works The End of Eddy and Who Killed my Father, from a self-writing perspective. To conduct this research, we investigated the formal and paratextual features - interviews, editorial information from the books, etc. - of the works, resting our arguments on Lejeune (2008). Next, we analyzed the composition of the narrative voice guided by Genette (2017), and, from that, the difference between author, narrator, and character, and the aspects related to the narrative time level, and person. To endorse the proposed discussion, the theorists Bal (1997), Friedman (2002), and Leite (2005) were integrated into it. Besides that, since it is a 21st -century narrative, we address in this dissertation the traditional narrator matter supported by Benjamin (1987) with the utilitarian and universal nature of literature, as well as the counterpoint, proposed by Santiago (2002), based on considerations on sexuality, and, above all, the social class of the author and narrator. Throughout this research, we conducted a bibliographical survey dedicated to the chosen works. With this work, we aim to contribute to the debate on self-writing and Édouard Louis’ literary works in Brazil.